2020
DOI: 10.1002/aelm.202000583
|View full text |Cite
|
Sign up to set email alerts
|

Detachable Flexible ISFET‐Based pH Sensor Array with a Flexible Connector

Abstract: systems for IoT, economical fabrication of devices is important. At a minimum, flexible devices currently require signal processing circuits and batteries to operate sensor systems. Integrating these into a sensor while maintaining mechanical flexibility is difficult without increasing the device cost. An approach to overcome this challenge is to separate the sensor system into two film parts: a disposable one for the printable low-cost sensor array and a reusable one for the expensive systems, including circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…[46] Oxides play an important role and form the foundation of the ISFET gates. [20,[47][48][49] The basic principle is that the H + released from the dynamic solution will affect the pH in the well. This induces a change in the surface potential of the oxide layer as well as the potential between the gate and base of the underlying field effect.…”
Section: Gate Materialsmentioning
confidence: 99%
“…[46] Oxides play an important role and form the foundation of the ISFET gates. [20,[47][48][49] The basic principle is that the H + released from the dynamic solution will affect the pH in the well. This induces a change in the surface potential of the oxide layer as well as the potential between the gate and base of the underlying field effect.…”
Section: Gate Materialsmentioning
confidence: 99%
“…The achieved sensitivity was 66.5 mV/pH, which has negligible effect of temperature. [512] Chou et al reported a work in which they had used nickel oxide as a sensing film on flexible arrayed pH sensor. They have improved the sensitivity by introducing oxygen gas during the sputtering process and the fabricated device shows the sensitivity of 63 mV/pH for pH range of 1-13.…”
Section: Flexible Isfetmentioning
confidence: 99%
“…[153] Honda et al designed a macroscale detachable pH sensor array that consists of a reusable, flexible ISFET array and a disposable flexible pH-sensitive membrane array through the flexible electrical connector, where ISFET is proposed to be extended gate geometry. [154] Figure 10k illustrates the optical image of a flexible 5 × 5 pH sensor array, in which polyaniline (PANI) is employed for a flexible pH-sensitive membrane because it has the capacity of low environment toxicity and can also detect protons by protonation/deprotonation effect on its film. The reaction between PANI and protons serves as potential pro-duction, leading to a variation of the transistor potential because PANI electrodes are combined with gate electrode through the flexible connectors.…”
Section: Active-matrix Array For Ph Sensingmentioning
confidence: 99%
“…Copyright 2022, American Association for the Advancement of Science. Reproduced with permission [154]. Copyright 2020, Wiley-VCH.…”
mentioning
confidence: 99%